2018
DOI: 10.1038/s41598-017-18329-3
|View full text |Cite
|
Sign up to set email alerts
|

Multi-valued and Fuzzy Logic Realization using TaOx Memristive Devices

Abstract: Among emerging non-volatile storage technologies, redox-based resistive switching Random Access Memory (ReRAM) is a prominent one. The realization of Boolean logic functionalities using ReRAM adds an extra edge to this technology. Recently, 7-state ReRAM devices were used to realize ternary arithmetic circuits, which opens up the computing space beyond traditional binary values. In this manuscript, we report realization of multi-valued and fuzzy logic operators with a representative application using ReRAM dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
92
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 133 publications
(94 citation statements)
references
References 40 publications
2
92
0
Order By: Relevance
“…https://doi.org/10.1371/journal.pone.0227454.g006 improve gemcitabine efficacy and decrease its side effects, here, we reported for the first time that a Smac mimetic enhanced gemcitabine-induced necroptosis in CCA cell lines. Smac mimetic-mediated sensitization to chemotherapeutic agent-induced apoptosis and necroptosis has been previously reported in several cancer cells and has been reported to suppress tumor growth in preclinical mouse models and early clinical trials of various cancers [47][48][49][50][51][52][53][54][55][56][57][58][59]70]. The results of a study in colon cancer in which the combination of a Smac mimetic and standard chemotherapeutic drugs, when a caspase inhibitor was blocked, were independent of necroptosis [25].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…https://doi.org/10.1371/journal.pone.0227454.g006 improve gemcitabine efficacy and decrease its side effects, here, we reported for the first time that a Smac mimetic enhanced gemcitabine-induced necroptosis in CCA cell lines. Smac mimetic-mediated sensitization to chemotherapeutic agent-induced apoptosis and necroptosis has been previously reported in several cancer cells and has been reported to suppress tumor growth in preclinical mouse models and early clinical trials of various cancers [47][48][49][50][51][52][53][54][55][56][57][58][59]70]. The results of a study in colon cancer in which the combination of a Smac mimetic and standard chemotherapeutic drugs, when a caspase inhibitor was blocked, were independent of necroptosis [25].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to previous studies, we found that gemcitabine induced caspase-independent cell death and was independent of the key necroptotic proteins RIPK1, RIPK3, and MLKL (S7 Fig). Accumulating evidence shows that small molecules that antagonize IAPs, Smac mimetics, greatly increase chemotherapy response to both apoptosis and necroptosis in cancer cells, although necroptosis has been far less examined [47][48][49][50][51][52][53][54][55][56][57][58][59]. We first examined the expression of cIAP1 and cIAP2 in a panel of CCA cells and found that both cIAP1 and cIAP2 were differentially expressed in CCA cell lines ( S5 Fig).…”
Section: Smac Mimetic and Gemcitabine Synergistically Trigger Necroptmentioning
confidence: 99%
“…Further, to enable uniform analog switching, fast speed, along with excellent retention properties, a thermal enhanced layer has been proposed to confine heat in switching layer [22]. Multi-state memristors have also been used for ternary arithmetic as well as native multi-valued logic implementation [23], [24]. Ot has been experimentally demonstrated that 3D-fabrication is feasible for resistive RAM arrays [25].…”
Section: Introductionmentioning
confidence: 99%
“…And(currentLiterals); 22 while All the activeCubes have not been computed; 23 result = XorReduction(activeCubes, result); 24 while Some cube has not been computed;…”
mentioning
confidence: 99%
“…The PSR method has the advantages of high specificity, sensitivity and rapidity under isothermal conditions over other established gene amplification methods. Until now, the PSR technique has been developed for bacteria (Liu et al, 2015 , 2018 ) yeast ( Candida albicans) and DNA viruses (canine parvovirus and Bovine herpesvirus-1) (Xiaoqun et al, 2016 ). PSR approach is based on strand displacement activity of Bst DNA polymerase enzyme, isolated from Bacillus stearothermophillus .…”
Section: Introductionmentioning
confidence: 99%